1068 Utilizing Lean Methodology To Improve The Sleep Study Results Turnaround Process. (27th April 2018) - Kunkel, H; Mullen, L; Robinson, N; Thomas, C; Morrow, K; Kaiser, M; Simakajornboon, N
Abstract: Introduction: Lean methodology has been used to review processes and eliminate duplicate and non-value added work. Our goal was to use lean methodology examine the administrative processes within the sleep program to improve information flow and right size he administrative staffing of the program. The process analyzed included the segment of work that occurred from the time the sleep report was interpreted by the sleep physician to the time it was released to the referring physician. Methods: A team of stakeholders was assembled including administrative staff, the business director, the business manager and a quality outcomes manager. Lean methodology was used as the problem-solving method. A value stream map was constructed and process step time studies were completed. Variations and non-value added steps in the process were documented. Results: Time studies revealed a lead-time of 36.5 minutes and processing time of 16.5 minutes per study resulting in 32.8 hours per week to complete this segment of the sleep study process. The value stream map was used to identify the following steps that could be reduced or eliminated: printing, manual documentation, standardizing physician styles in report processing; additionally we reassigned tasks to the most appropriate staff. Overall, lead-time and processing time were reduced by 17 and 5.25 minutes per sleep study, respectively, resulting in 13.7 hours of time saved per week. Conclusion: We reduced lead and processing time by 42% and found that Lean Methodology was critical to allow the team to break down the process in order to see areas of duplication or non-value added time. This revealed opportunities to standardize the process and eliminate the non-value added steps reducing the overall FTE needed to complete the administrative process of the sleep reports. Support (If Any):